AN UPDATED PHYTOCHEMICAL AND PHARMACOLOGICAL REVIEW ON GYNURA PROCUMBENS - KAMRAN ASHRAF (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Nowadays, the use of medicinal plants increased significantly for the aim of producing more effective drugs with fewer side effects. Gynura procumbens (family Asteraceae) is a high value medicinal plant with different properties that are considered less, regardless of having great therapeutic potential in traditional medicine. Many pharmacological studies have established the ability of this plant to exhibit antimicrobial, antioxidant, hepatoprotection, antigenotoxic, antiplasmodial, cytotoxic, cardioactive, antidiabetic, anti-inflammatory, etc. The aim of this study was to review the updated phytochemical, pharmacological investigations as well as the traditional and therapeutic uses of G. procumbens. Important and different experimental data have been addressed along with a review of most of the phytochemicals identified in this plant.